Use of the Internet and Mobile-Based "Apps" for Sex-Seeking Among Men Who Have Sex With Men in New York City. (November 2014) - Grosskopf, Nicholas A.; LeVasseur, Michael T.; Glaser, Debra B.
The Internet continues to be a popular venue for men who have sex with men (MSM) to seek sexual partners. Increased sexual risk behavior has been linked to MSM who use the Internet to seek partners. However, there has been little research on how new mobile-based social networking applications ("apps") may affect sex-seeking and sexual risk behaviors of MSM. One hundred twenty-six MSM in New York City were recruited to complete an online survey on the use of the Internet and other technology for sex-seeking. The authors collected data on variables of interest including sexual sensation seeking, gay identity affirmation, internalized homophobia, Internet/app use, and sexual behavior with men met via the Internet and mobile apps. Results indicated that men who use both the Internet and mobile apps to seek partners were younger and reported higher incomes ( p < .05) than men who used the Internet only. There were no significant differences between the groups with regard to race, sexual sensation seeking, gay identity affirmation, or internalized homophobia, indicating that the use of mobile-based apps for sex-seeking may be simply an example of evolving technologies. These findings may provide insight for the feasibility and planning of effective mobile app-based HIV/STI programs for MSM.